Design and implementation of a web-based online database of the U.P. Diliman Main Library's Index to Philippine Newspaper - Angeles, Chito N. (2006)
Applied research has not been a very popular type of research in the field of Library and Information Science (LIS). In general, most of the studies done in the field have been limited to basic researches. While basic research provides useful theories that can be applied to library processes, it does not produce viable applications.